Development ethics, deliberative democracy and environmental citizenship. The global challenge of sustaintability - Villarroel, Raúl (Revista de Filosofía, 2015)
This paper explores the notion of “citizenship” from a theoretical context showed by ecological problems, in order to face challenges posed by the alleged existence of an environmental anthropogenic devastation phenomenon that would be affecting our planet in nowadays. Some remarks about “environmental citizenship” are outlined, assuming the contemporary political philosophical point of view, since it extends the canonical concept of citizenship initially presented by Marshall